RNA-Seq and Gene Ontology Analysis Reveal Differences Associated With Low R/FR-Induced Shade Responses in Cultivated Lentil and a Wild Relative - Yuan, Hai Ying; Caron, Carolyn T.; Vandenberg, Albert; Bett, Kirstin E. (Frontiers in Genetics, 2022)
Lentil is an important pulse crop not only because of its high nutrient value, but also its ecological advantage in a sustainable agricultural system. Our previous work showed that cultivated lentil and wild lentil germplasm respond differently to light environments, especially low R/FR induced shade conditions. Little is known about how cultivated and wild lentils respond to shade at the level of gene expression and function. In this study, transcriptomic profiling of a cultivated lentil (Lupa, L. culinaris) and a wild lentil (BGE 016880, L. orientalis) at several growth stages are presented. De novo transcriptomes were assembled for both genotypes and differential gene expression analysis as well as gene ontology enrichment analysis were performed. The transcriptomic resources generated in this study provide fundamental information regarding biological processes and genes associated with shade responses in lentil. BGE 016880 and Lupa shared high similarity in their transcriptomes, however, differential gene expression profiles were not consistent between these two genotypes. Wild lentil BGE 016880 had more differentially expressed genes than cultivated lentil Lupa. Up-regulation of genes involved in gibberellin, brassinosteroid, and auxin synthesis and signaling pathways, as well as cell wall modification, in both genotypes explain their similarity in stem elongation response under the shade. Genes involved in jasmonic acid as well as flavonoid biosynthesis pathways were downregulated in BGE 016880 only, and biological processes involved in defense responses were significantly enriched in wild lentil BGE 016880 only. Down-regulation of WRKY and MYB transcription factors could contribute to the reduced defense response in BGE 016880 but not in Lupa under shade conditions. A better understanding of shade responses of pulse crop species and their wild relatives will play an important role in developing genetic strategies for crop improvement in response to changes in light environments.